Saga (2012), volume 4 ebook - Vaughan, Brian K. (Saga (2012), 2015)
THE #1 NEW YORK TIMES BESTSELLER RETURNS! Visit new planets, meet new adversaries and explore a very new direction, as Hazel becomes a toddler while her family struggles to stay on their feet. Collects SAGA #19-24.. Author: Brian K. Vaughan. Illustrator: Fiona Staples . 2014 Brian K. Vaughan & Fiona Staples.